2002
DOI: 10.1136/bmj.324.7350.1386
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement report: Effect of a scoring system and protocol for sedation on duration of patients' need for ventilator support in a surgical intensive care unit

Abstract: Relatively simple changes in sedation practice had significant effects on length of ventilator support. The change process was well received by the staff and increased their interest in identifying other areas for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(34 citation statements)
references
References 11 publications
1
30
0
3
Order By: Relevance
“…Indeed recent data from sedation studies have guided management of this important aspect of critical care. Target-based (27), protocolized sedation (28), with the incorporation of daily wake up trials (3, 29) have been shown to be associated with lower exposure to sedatives and analgesics and with improved outcomes and thus have been recommended as the “new standard of care” in sepsis management guidelines (30). Despite data being available for over 5 yr, recent large-scale sedation surveys from the United States (Ely EW, unpublished observations), Canada (31), and Europe (32) continue to show modest adherence at best to these standards and have shown that many ICU patients continue to be deeply sedated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed recent data from sedation studies have guided management of this important aspect of critical care. Target-based (27), protocolized sedation (28), with the incorporation of daily wake up trials (3, 29) have been shown to be associated with lower exposure to sedatives and analgesics and with improved outcomes and thus have been recommended as the “new standard of care” in sepsis management guidelines (30). Despite data being available for over 5 yr, recent large-scale sedation surveys from the United States (Ely EW, unpublished observations), Canada (31), and Europe (32) continue to show modest adherence at best to these standards and have shown that many ICU patients continue to be deeply sedated.…”
Section: Discussionmentioning
confidence: 99%
“…We found that sedation protocols are increasingly popular in Australasia, consistent with the results of international studies. 11,13,27 Although protocols have had dramatic beneficial effects on duration of mechanical ventilation and length of ICU stay in the United States and Europe, 21,22,38 recent Australian studies 19,20 had different findings. Differences in open or closed ICU models, nurse to patient ratios, nurses' education and autonomy, specialist medical training, and professional collaboration may be important factors in the international variation in outcomes for use of sedation protocols.…”
Section: Opinions On Sedation Managementmentioning
confidence: 99%
“…18 Interestingly, studies of the implementation of sedation protocols in Australian ICUs 19,20 indicate less beneficial patient outcomes (ie, ventilation time and ICU length of stay) than do similar European and American studies. 21,22 Therefore, we investigated doctors' and nurses' current practices and explored their opinions on sedation management of patients receiving mechanical ventilation in Australian and New Zealand ICUs to extrapolate potential explanations for these international differences in outcomes.…”
mentioning
confidence: 99%
“…Variable effectiveness within the ICU11 may be traced to published ICU reports whereby audit and feedback is undertaken in different ways: at the point-of-patient care in two,23 24 weekly in two,15 18 monthly in four,14 16–17 22 at a single time in one19 and not specified in two20 21 studies. Across reports, feedback is delivered through various channels including electronic, print and verbal processes.…”
Section: Introductionmentioning
confidence: 99%